1975
DOI: 10.1002/pssb.2220680234
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic emission in cadmium telluride

Abstract: The photoluminescent properties of free and bound excitons in high-purity p-and n-type CdTe single crystals are investigated in detail in connection with the dependence on excitation intensity, temperature, impurity-doping, and uniaxial stress. Intense free-exciton emission is observed in the single crystals grown from solutions and vapor epitaxial methods. From the thermal dissociation processes and the analysis on the basis of the effective mass argument developed by Sharma and Rodriguez and by Hopfield, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1

Year Published

1977
1977
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(47 citation statements)
references
References 14 publications
1
45
1
Order By: Relevance
“…The emission polarized with the electric vector parallel or perpendicular to the direction of stress was examined, but no splitting could be detected for either the I,-or the IYb-emission peaks. Applying the same stress to an unimplanted sample produced no change in the I,-exciton emission intensity but caused the emission to shift to longer wavelengths, as observed by Taguchi et al [6]. Our stress experiments on implanted samples are a t an early stage and are being continued.…”
Section: Resultssupporting
confidence: 58%
“…The emission polarized with the electric vector parallel or perpendicular to the direction of stress was examined, but no splitting could be detected for either the I,-or the IYb-emission peaks. Applying the same stress to an unimplanted sample produced no change in the I,-exciton emission intensity but caused the emission to shift to longer wavelengths, as observed by Taguchi et al [6]. Our stress experiments on implanted samples are a t an early stage and are being continued.…”
Section: Resultssupporting
confidence: 58%
“…In Ref. 38, the superlinearity of the BE emission was believed to arise from enhancement in the population of binding sites due to the neutralization of donors and acceptors by photoexcited carriers. Alternatively, it was suggested that the density of binding sites for BEs was constant with varying laser power and instead the observed superlinear power dependence of the exciton emission was due to the formation of excitons from free electrons and holes.…”
Section: Plmentioning
confidence: 99%
“…The grain boundaries in InSb for example have been systematically investigated by Haasen [29] and almost all the boundaries in a crystal have been shown to figure 8. At 5 K one can see near the band edge the donor exciton line at 1.5913 eV together with the acceptor exciton line at 1.5884 eV line [32,33]. The pairs.…”
mentioning
confidence: 94%